Characterization of Cu-mordenites with varying SiO2/Al2O3 ratios by 29Si-, 27Al-, 63Cu- and 1H-MAS NMR, optical absorption and catalytic activity for nitrogen oxide reduction; Biannual Conference on Chemistry, Chem 02, Faculty of Science, Department of Chemistry, Cairo University, Cairo, Egypt, March 4-7, 2002 - Petranovskii V.; Marzke R. F.; Diaz G.; Gomez A.; Pestryakov A. N. Aleksey Nikolaevich; Katada N.; Hernandez M. A.; Tamariz Florez J. V.; Bogdanchikova N.; Gurin V. (2002, 2002)
В фонде НТБ ТПУ отсутствует